Comparative structural analysis of polyurethane and silicone catheters of totally implantable venous access devices by micro-computed tomography. (November 2021) - Panetta, Daniele; Tollapi, Lara; Paolicchi, Adriana; Marri, Elisa; Aringhieri, Giacomo; Caramella, Davide
Objectives: To investigate microstructural alterations of explanted long-term central venous catheters of totally implantable venous access devices, using micro-computed tomography. Methods: A total of 16 catheters (9 made of silicone and 7 made of polyurethane), all non-fractured, have been analyzed in this study. Eight catheters were implanted for an average duration of 994 days (min–max: 98–2731 days), while the remaining eight catheters (four for each material, forming the SIref and PUref control groups) were analyzed before implant and used as a reference. X-ray micro-computed tomography was used to reconstruct the three-dimensional geometry of selected segments of each catheter (ca. 10 cm per sample). Results: Morphometric analysis of the catheters revealed increases wall thickness and section area in the polyurethane group as compared with the reference central venous catheters of the same materials (wall thickness: 403 ± 12 μm in the polyurethane (PU) group vs 382 ± 4 μm in PUref, p = 0.014; wall cross-section area: 2.04 ± 0.09 mm 2 in PU vs 1.91 ± 0.03 mm 2 in PUref, p = 0.04), whereas implanted silicone catheters showed a larger luminal cross section as compared with their controls (lumen cross-section area = 0.851 ± 0.020 mm 2 in silicone (SI) group vs 0.811 ± 0.007 mm 2 in SIref, p = 0.007). All analyzed samples in this study presented some type of alteration in the catheter walls, namely, hyperdense spots (below 0.1 mm size), air gaps/bubbles and displacements of inner and outer axes causing heterogeneous wall thickness. The incidence of air gaps showed no difference with respect to both material type and duration of implant, whereas the SI group revealed more hyperdense spots as compared to all other groups. Conclusion: Morphological change and local structural alteration can occur in both silicone and polyurethane catheters. This evidence suggests the need for further studies connecting those morphological changes with modification of mechanical robustness, which ultimately can play a role for patient safety.